2019
DOI: 10.1007/s12078-019-09273-9
|View full text |Cite
|
Sign up to set email alerts
|

Women Have Reduced Ability to Discriminate Body Odors During the Withdrawal Period of Oral Contraception

Abstract: Introduction Women’s olfactory perception varies across the menstrual cycle. The influence of oral contraceptives on this variability remains unclear. Methods To further estimate this, we assessed discrimination performance for both body odors and ordinary odorants in 36 women, 18 naturally ovulating, and 18 using oral contraceptives. Each participant was tested once a week over the course of a month, and data was then parsed into menstrual phases. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Our result, along with other evidence (Derntl et al, 2013;McNeil et al, 2013), compensates for this deficiency and demonstrates relatively better olfactory discrimination ability in the mid-luteal phase. It also complies with previous findings that female olfactory ability enhanced after oral contraceptive treatment (Derntl et al, 2013) and declined during the withdrawal period (Endevelt-Shapira et al, 2020), suggesting a promoting effect of ovarian hormones in olfaction, especially for highorder olfactory functions like discrimination (Hummel et al, 1997). However, the impact of hormonal contraceptives on the olfactory threshold, a more peripheral olfactory function, seems to vary with odor specificity (Lundstrom et al, 2006;Schaefer et al, 2021).…”
Section: Menstrual Cycle Modulates Female Olfactory Functionsupporting
confidence: 91%
“…Our result, along with other evidence (Derntl et al, 2013;McNeil et al, 2013), compensates for this deficiency and demonstrates relatively better olfactory discrimination ability in the mid-luteal phase. It also complies with previous findings that female olfactory ability enhanced after oral contraceptive treatment (Derntl et al, 2013) and declined during the withdrawal period (Endevelt-Shapira et al, 2020), suggesting a promoting effect of ovarian hormones in olfaction, especially for highorder olfactory functions like discrimination (Hummel et al, 1997). However, the impact of hormonal contraceptives on the olfactory threshold, a more peripheral olfactory function, seems to vary with odor specificity (Lundstrom et al, 2006;Schaefer et al, 2021).…”
Section: Menstrual Cycle Modulates Female Olfactory Functionsupporting
confidence: 91%
“…Moreover, albeit only marginally significant, women in the follicular phase reported a general higher awareness (i.e., higher SOS total score) toward social odors than women in the luteal phase. Accordingly, previous works reported higher sensitivity toward body odors during the follicular phase, compared with the luteal one [76,77] and, specifically, a preference for the odor of dominant and more attractive men [78][79][80]. Our results highlight that the reproductive menstrual phase affects not only the perception, but also the selfreported awareness toward social odors.…”
Section: Discussionsupporting
confidence: 70%
“…Also, OC seems to change partner body odor preference in women, shifting it from preferring the odor of men with a different major histocompatibility complex than oneself to men with a more similar major histocompatibility complex (Allen et al., 2019; Roberts et al., 2008; Wedekind et al., 1995). Similarly, withdrawal of OC has been linked to reduced discrimination for body odors, whereas no effects were found for ordinary odorants (Endevelt–Shapira et al., 2020). Because it has been demonstrated that olfactory perception fluctuates over the course of the menstrual cycle, and OC works by introducing exogenous hormones to interfere with this tightly orchestrated hormonal sequence, there is a well-grounded concern, as well as a potential mechanism, for OC to interfere with olfactory performance (Grillo et al., 2001; Lundström et al., 2006; Martinec et al., 2014).…”
mentioning
confidence: 99%